2018
DOI: 10.1097/aln.0000000000001997
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytic Therapy and Perioperative Considerations

Abstract: Fibrinolysis is a physiologic component of hemostasis that functions to limit clot formation. However, after trauma or surgery, excessive fibrinolysis may contribute to coagulopathy, bleeding, and inflammatory responses. Antifibrinolytic agents are increasingly used to reduce bleeding, allogeneic blood administration, and adverse clinical outcomes. Tranexamic acid is the agent most extensively studied and used in most countries. This review will explore the role of fibrinolysis as a pathologic mechanism, revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 99 publications
0
98
0
8
Order By: Relevance
“…7 Fibrinolytic shutdown that also occurs in sepsis is characterized by increased PAI-1 activity, resulting in low D-dimers. 31,32 Vascular endothelial injury not only causes further thrombocytopenia and reduction of natural anticoagulants, but also hemostatic activation as the phenotypic expression of thrombotic DIC. Analysis of septic patients who are coagulopathic and receive serine protease inhibitors such as antithrombin or thrombomodulin suggest that there may be a survival benefit in post hoc analyses.…”
Section: Inflammation and Coagulationmentioning
confidence: 99%
“…7 Fibrinolytic shutdown that also occurs in sepsis is characterized by increased PAI-1 activity, resulting in low D-dimers. 31,32 Vascular endothelial injury not only causes further thrombocytopenia and reduction of natural anticoagulants, but also hemostatic activation as the phenotypic expression of thrombotic DIC. Analysis of septic patients who are coagulopathic and receive serine protease inhibitors such as antithrombin or thrombomodulin suggest that there may be a survival benefit in post hoc analyses.…”
Section: Inflammation and Coagulationmentioning
confidence: 99%
“…In theory, AF should have its most favorable effect in those with hyperfibrinolysis. In contrast, hypercoagulability associated with fibrinolytic shutdown is reported to occur in 46% to over 64% of trauma patients [22][23][24][25][26][27][28][29][30][31][32] . On this basis alone, it is reasonable to propose that all patients likely do not benefit from TXA 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AF is often used in this population to minimize perioperative blood loss 42 . It is well established that AF therapy reduces bleeding and allogeneic transfusion requirements 29 . Myles et al studied the effectiveness of TXA versus placebo in a randomized control study of 4631 coronary-artery surgical patients and demonstrated that death or thrombotic complication occurred in 18.1% of placebo patients versus 16.7% of TXA patients 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid works as an anti-fibrinolytic agent by inhibiting the breakdown of polymer fibrin by plasmin, so that hemostasis can occur more effectively (Levy et al, 2018 Figure 1. et al, 2017).…”
Section: Bleeding Timementioning
confidence: 99%